Demotivating factors affecting the implementation of ISO 14001:2015 in Malaysia - Sorooshian, Shahryar; Lee, Sue Yee (John Wiley and Sons Inc., 2019)
Industrialization has brought with it environmental problems and the consequences of pollution, which has been affecting the world for decades. Immediate action is required to raise industry's awareness of its social responsibilities toward the environment. However, experience shows that companies that have obtained International Organization of Standardization (ISO) 14001:2015 certifications in Malaysia occupy but a small niche among the country's businesses. The purpose of this study is to assess the list of barriers and challenges to implementing and obtaining certifications under the ISO 14001:2015 Environmental Management System (EMS) by Malaysian firms. In addition, this study will rank these factors relative to their importance. This study is aimed at EMS experts at the Scientific and Industrial Research Institute of Malaysia (SIRIM QAS International Sdn. Bhd.). The study uses mathematical pairwise comparisons to generate the list of critical challenges and barriers. Therefore, the study is expected to raise environmental awareness among Malaysia's industries regarding the adoption of ISO 14001:2015 standards. Furthermore, the study provides a guideline for Malaysia's industries and policy‐makers to provide them with a better understanding of the barriers and challenges that companies face in implementing ISO 14001:2015 EMS, and at the same time, help them understand the need to eliminate the difficulties of standard implementation.